DARI 'LOGISTIC MANAGEMENT' MENUJU 'SUPPLY CHAIN MANAGEMENT' DAN TECHNOLOGY - Judith Felicia Irawan (Center for Economic Studies Universitas Katolik Parahyangan, 2003)
To procure materials, maintain in-process inventory and delivery products to customers, companies provided traditional logistics activities. Operational traditional logistics included inbound logistics, intern logistics and outbound logistics, the flow of physical goods, are being managed separately. In the time being, companies cannot handle many problems such as customer service satisfaction.To solve many problems, synchronized management of the flow of physical goods and associated information from sourcing to delivery products to customers, integrated logistics, being provided instead of operational traditional logistics. But problems stand still. Where is the product, now’?By separating the flow of physical goods and the flow of information through information technology, problem can be answered. Supply Chain Management and Technology.Traditional Logistics Integrated Logistics Supply Chain Management